The Evolution of Male-Female Wages Differentials in Canadian Universities: 1970-2001 - Casey Warman; Frances Woolley; Christopher Worswick (Queen's University, Department of Economics, 2006)
In this paper, we use a unique data set containing detailed information on all full-time teachers at Canadian universities over the period 1970 through 2001. The individual level data are collected by Statistics Canada from all universities in Canada and are used to analyze the evolution of male-female wage differentials of professors in Canadian universities. The long time series aspect of this data source along with the detailed administrative information allow us to provide a more complete and more accurate portrait of the wage gap than is available in most other studies. The results of a cohort-based analysis indicate that the male salary advantage among university faculty has declined for more recent birth cohorts. This has been driven not so much by an increase in the real salaries of female professors but from a cross cohort decline in the earnings of male professors and the fact that female professors have not experienced a similar cross cohort decline. Also important to note is the fact that the differences across cohorts appear to be permanent. There is no clear pattern of changes in these cohort differences with age.
Keywords: J16; J31; J71; 330; gender; earnings; Canada; professors; faculty; Lohnstruktur; Geschlechterdiskriminierung; Hochschullehrer; Kanada